Characteristics of Nitrate Reduction in a Mutant of the Blue-Green Alga Agmenellum quadruplicatum - Stevens, S. E. (1973)
Characteristics of nitrate reduction in terms of nitrite production in an N-methyl-N′-nitro-N-nitrosoguanidine-induced mutant of the blue-green alga Agmenellum quadruplicatum are described. Following induction of nitrate reduction a linear rate of nitrite production proportional to cell concentration was observed. Rate of nitrite production and growth rate showed similar responses to pH, temperature, and light intensity. If required, only trace amounts of carbon dioxide were necessary for nitrite production. Atmospheres of oxygen or nitrogen inhibited production of nitrite. In addition, a low but constant rate of nitrite production was observed in the dark. Nitrite production by mutant AQ-6 was studied in terms of photosynthesis. As nitrite production proceeded, rate of photosynthesis declined. Ultraviolet irradiation and 3-(3,4-dichlorophenyl)-1, 1-dimethylurea poisoning did not prevent nitrite production. The action spectrum of nitrite production was chlorophyll a-like.